(5E)-5-(2,4-Dichlorobenzylidene)-2-(piperidin-1-yl)-1,3-thiazol-4(5H)-one - Fun, Hoong-Kun (International Union of Crystallography, 2011)
In the title compound, C(15)H(14)Cl(2)N(2)OS, the piperidine ring adopts a chair conformation. The dihedral angle between the thiazolidine ring and the dichlorobenzene ring is 9.30 (4)°; this near coplanar conformation is stabilized by the formation of an intramolecular C—H⋯S hydrogen bond, which generates an S(6) ring. In the crystal, molecules are linked by C—H⋯O hydrogen bonds, forming [001] chains. Weak π–π interactions [centroid–centroid separation = 3.5460 (5) Å] consolidate the structure.